Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines the implications of lower crude oil prices on Malaysia's economy. Although Malaysia's net oil exports are now very small as a share of GDP, its gas exports are sizeable. The paper provides some background on the structure of energy production and trade in Malaysia, and presents results from empirical analysis of the oil prices on Malaysia's growth. It is concluded that the decline in prices is likely to have a net negative impact on growth, even though the recent decline in oil prices partially reflects supply considerations.